A functional serotonin transporter promoter gene polymorphism increases ADHD symptoms in delinquents: Interaction with adverse childhood environment - Retz, Wolfgang; Freitag, Christine M.; Retz-Junginger, Petra; Wenzler, Denise; Schneider, Marc; Kissling, Christian; Thome, Johannes; Rösler, Michael (Psychiatry research, 2008)
Although attention-deficit/hyperactivity disorder (ADHD) is highly heritable, environmental conditions play an important role in its manifestation during childhood development. Here, we report the results of an investigation on the interaction of adverse childhood environment with a functional polymorphism of the serotonin transporter promoter gene (5-HTTLPR) and its impact on ADHD psychopathology in young adult delinquents. Standardized instruments were used to assess childhood and current ADHD and adverse childhood environment in 184 male delinquents. Each subject was genotyped for 5-HTTLPR long (L) and small (S) alleles. Logistic regression analysis revealed independent effects of high childhood environmental adversity and the 5-HTTLPR LL-genotype on self-reported childhood ADHD and on persistent ADHD. In addition, a significant gene by environment interaction was found, indicating that carriers of at least one 5-HTTLPR short allele are more sensitive to childhood environment adversity than carriers of the LL-genotype. The results support prior findings of association between ADHD and 5-HTTLPR LL-genotype and adverse childhood environment, and they underline the need for further investigation of gene by environment interaction with respect to ADHD.